Whole-Exome Sequencing Uncovers Specific Genetic Variation Difference Based on Different Modes of Drug Resistance in Small Cell Lung Cancer - Tang, Ning; Li, Zhenzhen; Han, Xiao; Zhao, Chenglong; Guo, Jun; Wang, Haiyong (Frontiers in Oncology, 2022)
The poor survival rates of SCLC is mainly related to the condition that patients with SCLC often achieve exhilarating responses to first-line chemotherapy, but most patients relapse rapidly owing to resistant to further treatment. In this study, we attempted to analysis the data of the whole exome sequencing based on the largest sample size currentl to develop a classifier to predict whether a patient will be chemorefractory or chemosensitive and to explicate the risk of recurrence which affects the prognosis of patients. We showed that the different characteristics of somatic mutational signatures, somatic mutation genes, distinct genome instability , between chemorefractory and chemosensitive SCLC patients. Amplified mutations in the chemosensitive group inhibited regulation of cell cycle process, transcription factor binding, B cell differentiation. Analysis of deletion mutation also suggested that the detection of the chromosomal-level variation might influence our treatment decisions. Higher PD-L1 expressions (based on TPS methods) were mostly present among the chemosensitive patients ( p = 0.026), while PD-L1 expressions (based on CPS methods) and CD8+ TILs were no differences between two groups. According to the model determined by logistic regression, each sample was endowed with a predictive probability value (PV). Then samples were divided into high risk group (＞ 0.55) and low risk group(≤0.55), and the survival analysis were obvious differences between groups. It provides a reference basis to translate this knowledge into practice and thus benefit for Chinese patients with SCLC to formulate personalized treatment plans.